Neural correlates of distraction and conflict resolution for nonverbal auditory events - Hannah J. Stewart (Nature Portfolio, 2017)
Abstract In everyday situations auditory selective attention requires listeners to suppress task-irrelevant stimuli and to resolve conflicting information in order to make appropriate goal-directed decisions. Traditionally, these two processes (i.e. distractor suppression and conflict resolution) have been studied separately. In the present study we measured neuroelectric activity while participants performed a new paradigm in which both processes are quantified. In separate block of trials, participants indicate whether two sequential tones share the same pitch or location depending on the block’s instruction. For the distraction measure, a positive component peaking at ~250 ms was found – a distraction positivity. Brain electrical source analysis of this component suggests different generators when listeners attended to frequency and location, with the distraction by location more posterior than the distraction by frequency, providing support for the dual-pathway theory. For the conflict resolution measure, a negative frontocentral component (270–450 ms) was found, which showed similarities with that of prior studies on auditory and visual conflict resolution tasks. The timing and distribution are consistent with two distinct neural processes with suppression of task-irrelevant information occurring before conflict resolution. This new paradigm may prove useful in clinical populations to assess impairments in filtering out task-irrelevant information and/or resolving conflicting information.